(untitled) (TEL Tempo, Espaço e Linguagem, 2023)
Paid domestic work performed by internal immigrant women in Brazil is unique in circumscribing these social subjects to social markers of differentiation. To understand how these women, through the workshop, especially through the transmission of films, group dynamics and the discussion of issues related to paid domestic work and their insurgent voices are the focus of analysis to revive the valorization and recognition of their profession and their political and cultural experiences as strategies for social emancipation, from an interdisciplinary, intersectional, decolonial and pluriversal perspective.